A Study on Architectures for Embedded Devices - Radhakrishnan, Arun; T. Muralikrishna (International Journal of Computer Sciences and Engineering, 2014)
Embedded designers canï¿½t afford ï¿½the blue screen of death.ï¿½ Desktop operating systems can get rebooted every so often, but embedded devices often have to run for years without a single reboot. Devices that are used in medical fields are one of the most appropriate examples in which reliability is more important. Also other embedded devices such as industrial-automation systems, security systems and automotive systems have to be more reliable. And the heart of the embedded system is the processor used in it. In recent days there is a big debate among the embedded device manufacturers in selecting the type of architectures which can be used in their embedded devices. The two most commonly used architectures in embedded devices are X86 and ARM. The decision to chose X86 or ARM needs to be investigated thoroughly based on their advantages and limitations. The selection is not only based on its performance of processors and costs but also on power consumption, the type of hardware and software components that it can support and the type of input and output devices supported. In this paper both the architectures are analyzed.